Discurso e argumentação no programa televisivo Vitória em Cristo de Silas Malafaia - Ferraz, Sarah Menoya (Universidade Federal de São Carlos, 2014)
The purpose of this thesis is to verify, according to the theoretical assumptions of Discourse Analysis of French tradition, the Pentecostal discourse of televangelism Victory in Christ. This work will aim its constituent character and analyze the enunciative scenes that constitute the discourse, and from that, it will build relationships between its initial discursive formation and remoteness and proximity to other discursive formations. The research corpus consists of six views of the televangelism mentioned above. We consider the concepts of Dominique Maingueneau about constituent discourses; ethos and scene of enunciation; citation and Detachment; Hyperenunciator and Thesaurus Bible; community discursive and positioning . Adds up , in the background , the analysis and description of the arguments used by the enunciator according to the concepts of Pereleman and Tyteca , enrolled in Argumentation Theory, since the arguments are considered constituent elements of enunciative scenes, in other words , they integrate the scene is validated on account of its uses . Among the main events displayed on observation analyzed data are: a discourse of classical Pentecostalism approaching the Pentecostal discursive formation, the use of arguments in relation to what is known about an auditorium with little education and low social status and processing of speech for their accommodation to contemporary society.
Keywords: Análise do discurso; Teoria da argumentação; Televangelho; Discourse analysis; Argumentation theory; Televangelism; LINGUISTICA, LETRAS E ARTES::LINGUISTICA